PENGARUH PENGARUH PEMASARAN DIGITAL MELALUI LAYANAN LIVE SHOWROOM TERHADAP BRAND IMAGE - Shania Yusita Puspa Melati; Rosita Anggraini (CV. Shofanah Media Berkah, 2023)
Abstact. The trend of digitalization is getting stronger and has a stronger impact on changes in all fields, the automotive sector is one of them. Currently, online platforms are very important for automotive entrepreneurs, including Toyota. PT Toyota Astra Motor presents a total mobility solution as a marketing communication strategy through digital transformation, namely launching a digital showroom. Digital showroom namely Toyota live showroom. The research objective was to determine the effect of digital marketing through Toyota live showroom services on brand image. The population that was the subject of this study were 1,350 TOYOTA Live Showroom users (TOYOTA Live Showroom users in 2022). The sampling technique used was simple random sampling. Determination of the minimum number of samples that represent the population in the study used the Slovin formula. The sample in this study were 93 TOYOTA Live Showroom users. Data collection was carried out using a questionnaire with survey techniques for TOYOTA Live Showroom users. The research paradigm is positivistic with a data analysis approach. This research uses reliability tests, validity tests, simple linear regression analysis, correlation analysis, coefficient of determination, and T-test. The results of this study indicate that the digital marketing variable (X) has a partial impact significant to the Brand Image of PT Toyota Astra Motor by 60.5% (quite strong). Based on the data obtained, it is known that the R square value is 0.605. This indicates that the digital marketing variable (X) simultaneously has a 60.5% (moderate) influence on the brand image variable (Y). while the rest (100% -60.5% = 39.5%) is influenced by other variables not examined in this study. Keywords: Marketing, Digital Marketing, Brand Image.